THE ROLE OF ARTICLE XX OF THE GENERAL AGREEMENT ON TARIFFS AND TRADE (GATT) 1994 IN COMBATING ILLEGAL FISHING ACTIVITY : A CASE STUDY OF THE UNITED STATES OF AMERICA - Intan Purnama; Wardah Wardah (Jurnal Ilmiah Mahasiswa Bidang Hukum Kenegaraan, 2018)
Article XX (b) and (g) of the GATT 1994 regulates about general exceptions measures, that allow the WTO members to take legal action in rejecting the products from certain states. The rejection could be applied by using some categories, particularly to protect human, animal and plant life or health, and also relating to the conservation of exhaustible natural resources. The United States of America (USA) has implemented the article, to protect its domestic market from illegal fishing imported products.This research aims to describe the arrangement of Article XX of the GATT 1994 in combating the illegal fishing activity and to identify how the implementation of Article XX regulates illegal fishing activity in the USA. This research used normative legal research. Data was obtained from library research would be processed systematically to attain appropriate depiction with the research problems. The data subsequently would be analyzed by using qualitative method that means using secondary data that consist of primary legal material, secondary legal material and tertiary legal material, so it can be acquired objective analysis to answer problems raised. The result of this researchindicates that the arrangement of the Article XX (b) and (g) of GATT 1994 can be used to combat illegal fishing activity. The article also related to national regulations. As long as related with the article, the national rules still could be implemented. Therefore, the USAcan use the article to reject of imported products whichcome from illegal fishing. Presently, the effort that has been made by international government and local government of the USA is insufficient to protect the living creatures in the sea. In addition, the WTO should do the amendment in the Article XX of the GATT 1994 about spesific explanation rare spesies animals or plants which states has protect it. Then, the USA should has a national rules which related to prevent illegal fishing trading to support the article that is implemented. By applying this article, the USA could prevent their market from illegal fishing imported products.